2001
DOI: 10.1097/00000539-200111000-00060
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Does Not Prolong the Analgesia of 20 mL Ropivacaine 0.5% or 0.2% in a Femoral Three-In-One Block

Abstract: We evaluated the effect of epinephrine on the duration of analgesia of 20 mL ropivacaine 0.5% or 0.2% injected in femoral three-in-one block for pain relief after total knee replacement. Our results show that epinephrine does not alter the duration of analgesia of the two solutions investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 14 publications
4
37
0
1
Order By: Relevance
“…Low concentrations of ropivacaine (0.063-0.5 %) injected intradermally (0.1 ml) caused vasoconstriction, but at higher concentration (1 %) did not have same effect [5,6]. Earlier studies on animals and humans have shown that addition of vasoconstrictive agent to ropivacaine did not result in any additional benefit [7]. The vasoconstrictive effect at low concentrations is likely to contribute to its duration of action in dental anesthesia, but the question of its influence on cardiovascular parameters remains as studies on volunteers and animals have reported contradictory results for the cardiovascular effect of ropivacaine [8].…”
Section: Discussionmentioning
confidence: 93%
“…Low concentrations of ropivacaine (0.063-0.5 %) injected intradermally (0.1 ml) caused vasoconstriction, but at higher concentration (1 %) did not have same effect [5,6]. Earlier studies on animals and humans have shown that addition of vasoconstrictive agent to ropivacaine did not result in any additional benefit [7]. The vasoconstrictive effect at low concentrations is likely to contribute to its duration of action in dental anesthesia, but the question of its influence on cardiovascular parameters remains as studies on volunteers and animals have reported contradictory results for the cardiovascular effect of ropivacaine [8].…”
Section: Discussionmentioning
confidence: 93%
“…Clonidine [114] NS at rest or on movement compared with no clonidine Adrenaline [115] NS compared with no adrenaline Ropivacaine [30,92], bupivacaine [30,92] NS Timing of administration Oral and IV conventional NSAID [10] NS pre-+ postoperative vs postoperative administration Lumbar epidural bupivacaine plus opioid [116] NS pre-+ postoperative vs postoperative administration Lumbar epidural lidocaine plus ketamine plus morphine [111] Inconclusive results pre-vs post-incision Intra-articular bupivacaine [94] NS pre-vs postoperative techniques. The systemic analgesia trials compare active intervention groups of analgesics [paracetamol, conventional non-steroidal anti-inflammatory drugs (NSAID), COX-2-selective inhibitors, weak opioids, and strong opioids] with either a control or placebo group.…”
Section: Ns Components Of Spinal Solutionmentioning
confidence: 99%
“…According to our previous report where duration of analgesia with 20 mL ropivacaine 0.5% was 657 ± 345 min, 13 the sample size was computed to detect an increase of duration of 50%, i.e., 5 ½ hr with a power of 80% or greater and a 5% or less chance of a type 1 error (ß = 0.2; two-tailed α = 0.05). For four study groups a minimal sample of 18 patients per group met these criteria.…”
mentioning
confidence: 99%
“…1,2,13,16-19 Among these, only one reported the duration of analgesia of the initial dose of local anesthetic, 13 only one reported extent of the block, 16 and a dose response study has never been described previously. Our study in patients undergoing TKR demonstrates that there was no significant difference in duration of analgesia between the four anesthetic solutions studied.…”
mentioning
confidence: 99%